(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Jaghri Bek was one of the Seljuk family princes, and led the armies against his opponents after the death of his father Michael, Sometimes he failed, but he often succeeded, His military efforts and courage in the turnout of the battles he fought against his opponents had a great impact on the success of the Seljuk Turkmen from success, Which was embodied in the Declaration of the establishment of their independent state in 429 AH / 1038 AD, Even after the declaration of that State, his previous efforts had not ceased, But continued until his death, he undertook to protect the eastern border against their opponents, He also made himself an example of the rest of the Seljuk princes in presenting the interest of the state to personal interests, Therefore, he was one of the most important pillars of the Seljuk state, and the influential factor in its establishment and ensuring its continuity. يعد جغري بك من أمراء الأسرة السلجوقية، وأحد أبرز قادتها، أخذ على عاتقه قيادتها عسكرياً ضد خصومها بعد وفاة والده ميكائيل، فخطط ودبر وتولى قيادة أبناء قبيلته في الحروب التي خاضوها مع باقي القوى السياسية التي كانت متواجدة حينها في مشرق العالم الإسلامي، أخفق أحياناً، لكنه نجح في أحيان كثيرة، فكانت لجهوده العسكرية وشجاعته في الإقبال على المعارك التي خاضها دون هوادة ضد خصومه، الأثر الكبير فيما حققه التركمان السلاجقة من نجاح، والذي تجسد في إعلان قيام سلطنتهم المستقلة سنة 429هـ/ 1038م، ولم تتوقف نشاطاته بعد قيام سلطنتهم، بل استمرت إلى حين وفاته، فقد أخذ على عاتقه حماية حدودها الشرقية ضد خصومها، كما جعل من نفسه قدوة لباقي الأمراء السلاجقة في تقديم مصلحة السلطنة على المصالح الشخصية، فكان بذلك من أهم دعائم السلطنة السلجوقية، والعامل المؤثر في قيامها وضمان استمرارها.